2011
DOI: 10.1002/app.33480
|View full text |Cite
|
Sign up to set email alerts
|

Swelling and drug release profile of poly(2‐ethyl‐2‐oxazoline)‐based hydrogels prepared by gamma radiation‐induced copolymerization

Abstract: Poly(2-ethyl-2-oxazoline) and acrylic acid were copolymerized in different compositions using crays-induced polymerization and cross-linking to obtain a series of pH-sensitive hydrogels. The preparation parameters that may affect the copolymerization process such as the feed solution composition and irradiation dose were optimized. Swelling characteristics of the obtained polymeric hydrogels were evaluated. The results show the significant effects of the hydrogel composition, soaking time, and pH on the swelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The authors use Ibuprofen as a model drug and give a proof on concept on the use of POx based hydrogels as controlled release modality for drug delivery to the gut. [193] Also Wiesbrock and co-workers reported on POx hydrogels with intended use stimuli-triggered drug delivery. In this case a model compound, eosin Y was released over time as the hydrogel decomposes.…”
Section: Other Drug Delivery Modalitiesmentioning
confidence: 99%
“…The authors use Ibuprofen as a model drug and give a proof on concept on the use of POx based hydrogels as controlled release modality for drug delivery to the gut. [193] Also Wiesbrock and co-workers reported on POx hydrogels with intended use stimuli-triggered drug delivery. In this case a model compound, eosin Y was released over time as the hydrogel decomposes.…”
Section: Other Drug Delivery Modalitiesmentioning
confidence: 99%
“…Of the limited research examining cross-linked POx, the pioneering studies were reported by the group of Seagusa who cross-linked partially hydrolyzed PMeOx using a variety of reversible and nonreversible methods or cross-linked through the use of bis-2-oxazoline comonomers. Some of these studies were performed in aqueous conditions, but no biological applications were considered. More recently, cross-linking of PEtOx via γ-irradiation and microwave-assisted copolymerization with bis-2-oxazoline has been reported although neither of these approaches are suitable for encapsulation of cells or for use with fragile proteins. Other cross-linking approaches using POx as a copolymer or blend have been recently reviewed by Kelly and Wiesbrock …”
Section: Introductionmentioning
confidence: 99%
“…El‐Hag Ali and AlArifi prepared poly(2‐ethyl‐2‐oxazoline) (PEtOx)‐based hydrogels using gamma irradiation and characterized them with regard to their swelling profile and capacity, pH‐sensitivity and possible applicability as a colon‐specific drug delivery system, using ibuprofen as a model drug.…”
Section: Sterilization Of Hydrogel‐based Medical Devicesmentioning
confidence: 99%